2013
DOI: 10.1073/pnas.1220865110
|View full text |Cite
|
Sign up to set email alerts
|

Functionally distinct Gata3/Chd4 complexes coordinately establish T helper 2 (Th2) cell identity

Abstract: GATA binding protein 3 (Gata3) is a GATA family transcription factor that controls differentiation of naïve CD4 T cells into T helper 2 (Th2) cells. However, it is unknown how Gata3 simultaneously activates Th2-specific genes while repressing those of other Th lineages. Here we show that chromodomain helicase DNA-binding protein 4 (Chd4) forms a complex with Gata3 in Th2 cells that both activates Th2 cytokine transcription and represses the Th1 cytokine IFN-γ. We define a Gata3/Chd4/p300 transcriptional activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 35 publications
0
69
0
Order By: Relevance
“…Multiple transcription factors including Miz-1 and GATA3 have been found to act as both a transcriptional activator and repressor. It was reported that whether they function as a transcriptional activator or a repressor depends on their interactions with other transcriptional regulators (32,33). Spi-B expression endows lung cancer cells with two properties that are normally required for expansion of developmentally mature B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple transcription factors including Miz-1 and GATA3 have been found to act as both a transcriptional activator and repressor. It was reported that whether they function as a transcriptional activator or a repressor depends on their interactions with other transcriptional regulators (32,33). Spi-B expression endows lung cancer cells with two properties that are normally required for expansion of developmentally mature B lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Clone, D10G4.1-FLAG-tagged Gata3 proteins were purified from D10G4.1 as described previously (18). The proteins were digested with trypsin.…”
Section: Identification Of the Methylation Sites Of Gata3 In The Th2mentioning
confidence: 99%
“…Immunoprecipitation and Immunoblotting-Immunoprecipitation was performed as described previously (18). After electrophoresis, the proteins were subjected to immunoblotting as described previously (37).…”
Section: Identification Of the Methylation Sites Of Gata3 In The Th2mentioning
confidence: 99%
See 2 more Smart Citations